Investigation into CYP3A4-mediated drug–drug interactions on midostaurin in healthy volunteers - Dutreix, Catherine; Munarini, Florence; Lorenzo, Sebastien; Roesel, Johannes; Wang, Yanfeng (Cancer chemotherapy and pharmacology, 2013)
Purpose Midostaurin (PKC412), a multitargeted tyrosine kinase inhibitor that targets FMS-related tyrosine kinase 3 and KIT, is in clinical trials for the treatment for acute myeloid leukemia and advanced systemic mastocytosis. In vitro studies showed that midostaurin is predominantly metabolized by cytochrome P450 3A4 (CYP3A4) and that midostaurin inhibits and/or induces the same enzyme. Here, we address the clinical relevance of CYP3A4-related drug–drug interactions with midostaurin as either a “victim” or “perpetrator.” Methods Three phase I studies in healthy volunteers evaluated the effects of a CYP3A4 inhibitor (ketoconazole 400 mg daily for 10 days) or CYP3A4 inducer (rifampicin 600 mg daily for 14 days) on concentrations of midostaurin and its metabolites following a single 50-mg dose of midostaurin and the effects of midostaurin as a single dose (100 mg) and multiple doses (50 mg twice daily) on midazolam (a sensitive CYP3A4 probe) concentration. The plasma concentrations of midostaurin and its 2 active metabolites, CGP62221 and CGP52421, were determined using a sensitive liquid chromatography/tandem mass spectrometry method. Results Inhibition of CYP3A4 by ketoconazole increased midostaurin exposure more than tenfold, and induction of CYP3A4 by rifampicin decreased midostaurin exposure by more than tenfold. Midostaurin did not appreciably affect the concentrations of midazolam or its metabolite, 1′-hydroxymidazolam, at single or multiple doses. Conclusion The pharmacokinetics of midostaurin and its metabolites was affected substantially by ketoconazole and rifampicin, suggesting that midostaurin is a sensitive CYP3A4 substrate. Midostaurin did not appear to inhibit or induce CYP3A4 in vivo.